Photoluminescent behavior of SrZrO3/SrTiO3 multilayer thin films - Moreira, M. L.; Andres, J.; Longo, V. M. [UNESP]; Li, M. S.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Elsevier B.V., 2009)
A detailed investigation was made into the origin of photoluminescence in an alternate multilayer system of SrZrO3 (SZO) and SrTiO3 (STO) thin films. XRD and room-temperature PL studies revealed a high consistency with respect to improved crystallization at elevated temperatures. The photoluminescence behaviour of SZO/STO multilayered system consists in the superposition of independent photoluminescence emissions of both STO and SZO films. Based on the present results and on previous experimental and theoretical data, we propose that the origin of the photoluminescence emission results from structural disorder generated by the presence of distortions in the ideal constituent clusters of these materials. (c) 2009 Elsevier B.V. All rights reserved.